2023
DOI: 10.35816/jiskh.v12i1.1022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ethanol Extract of Tomato (Solanum lycopersicum L.) on Staphylococcus epidermidis in vitro

Abstract: Tomato is one of the plants that contain lycopene as an antibacterial. Acne is an infectious disease caused by Staphylococcus epidermidis. Antibiotic treatment starts to become resistant so that plants can be used as alternative treatments. The study aimed to determine the effectiveness of the ethanolic extract of tomato (Solanum lycopersicum L) against the growth of Staphylococcus epidermidis bacteria in vitro. This type of research is experimental. Extraction was carried out by maceration method with 96% eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
0
0
Order By: Relevance
“…18 The study to determine the effectiveness of the ethanolic extract of tomato (Solanum lycopersicum L) against the growth of Staphylococcus epidermidis bacteria in vitro, showed that the diameter of the inhibition zone formed in the positive control was 40.36 mm (potent inhibition), inhibition zones at concentrations of 100, 80, 60, 40, and 20% had solid inhibitory power. 19 Mouth rinses are the most usual and easy way for antiplaque agents to be delivered. The direct damage to oral health, xerostomia seemed independently associated with mouthwashes, may have an effect on these chemical compounds.…”
Section: Introductionmentioning
confidence: 99%
“…18 The study to determine the effectiveness of the ethanolic extract of tomato (Solanum lycopersicum L) against the growth of Staphylococcus epidermidis bacteria in vitro, showed that the diameter of the inhibition zone formed in the positive control was 40.36 mm (potent inhibition), inhibition zones at concentrations of 100, 80, 60, 40, and 20% had solid inhibitory power. 19 Mouth rinses are the most usual and easy way for antiplaque agents to be delivered. The direct damage to oral health, xerostomia seemed independently associated with mouthwashes, may have an effect on these chemical compounds.…”
Section: Introductionmentioning
confidence: 99%